Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Terre(s) des femmes? - Institut de recherches et d'études féministes (FéminÉtudes, 1996)
Cette publication de 1996 aborde les identités et les théories postmodernes de la fin du XXe siècle en études féministes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; droits des femmes*; féminétudes; histoire et politique; intersectionnalité; militance; postmodernisme; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences